Law, migration, and human mobility : mobile law - Kmak, Magdalena (Routledge, 2023)
"This book analyses the multifaceted ways law operates in the context of human mobility, as well as the ways in which human mobility affects law. Migration law is conventionally understood as a tool to regulate human movement across borders, and to define the rights and limits related to this movement. But drawing upon the emergence and development of the discipline of mobility studies, this book pushes the idea of migration law towards a more general concepts of mobility that encompass the various processes, effects, and consequences of movement in a globalized world. In this respect, the book pursues a shift in perspective on how law is understood. Drawing on the concepts of 'kinology' and 'kinopolitics' developed by Thomas Nail as well as 'mobility justice' developed by Mimi Sheller, the book considers movement and motion as a constructive force behind political and social systems; and hence stability that needs to be explained and justified. Tracing the processes through which static forms, such as state, citizenship, or border, are constructed and how they partake in production of differential mobility the book challenges the conventional understanding of migration law. More specifically, and in revealing its contingent and unstable nature, the book reveals how human mobility is itself constitutive of law. This interdisciplinary book will appeal to those working in the areas of migration and refugee law, citizenship studies, mobility studies, legal theory, and sociolegal studies"--